A comparative analysis of the meaning of 'mining operations' for income tax purposes - Fourie, Christine (Department of Finance and Tax, 2018)
The South African ("SA") mining industry played (and continues to play) a pivotal role in the development of the SA economy. It is therefore no surprise that the industry has long been the beneficiary of favourable tax concessions. One of these favourable tax concessions is the 100% capital expenditure allowance. Access to this allowance is dependent on the interpretation of the definition of "mining operations" in section 1(1) of the Income Tax Act, No. 58 of 1962 ("the ITA"). Currently, there is legal uncertainty in SA regarding the meaning of "mining operations". This is so because central to the term "mining operations" is the term "mineral", which is not defined in the ITA, nor does it have an ordinary fixed meaning. SA courts have further not authoritatively dealt with the meaning of "mining operations" despite being presented with the opportunity to do so in recent case law. This legal uncertainty is further fuelled by a recent draft interpretation note issued by the South African Revenue Service ("SARS"), expressing the view that quarrying operations for inter alia clay for brickmaking and limestone for the manufacture of cement, do not constitute "mining operations". Practically, this legal uncertainty may act as a deterrent to mining companies incurring capital expenditure, essentially curbing the development of the SA mining industry. This study seeks to analyse the different meanings attributed by SARS, SA academic writers and SA courts to the definition of "mining operations" (and the related meaning of "mineral") for income tax purposes. The purpose of this analysis is to determine whether the extraction of clay for brickmaking and limestone for the manufacture of cement constitutes "mining operations". Against this background, Australian legislation and case law on the interpretation of the term "mining operations" and "mineral" will be studied in order to draw a comparison between SA and Australia's treatment of "mining operations". This study further interprets the meaning of "mining operations" through the application of the Savignian interpetation model in terms of which it is concluded that useful guidance can be sought by SA from Australian jurisprudence when interpreting the meaning of the term "mining operations" for income tax purposes and that the purposive test applied in Australia should be adopted by SA courts. Based on the application of this guidance, the key finding of this dissertation is that the extraction of clay for brickmaking and limestone for the manufacture of cement should in principle qualify as "mining operations" and that the capital expenditure incurred in this regard should be eligible for the 100% capital expenditure allowance.